2006
DOI: 10.1099/jmm.0.46072-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular characterization of mannitol salt positive, coagulase-negative staphylococci from nasal samples of medical personnel and students

Abstract: The identification of mannitol salt positive, coagulase-negative staphylococci (CNS) is often disregarded when Staphylococcus aureus is screened in clinical samples using mannitol salt agar. However, the emergence of CNS as important human pathogens has indicated that reliable methods for the identification of clinically significant CNS are of great importance in understanding the epidemiology of infections caused by them. The identification and molecular characterization of mannitol salt positive CNS from nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 60 publications
4
41
0
2
Order By: Relevance
“…Species identification has been done by ITS PCR, which has proven to be a reliable tool (8,16). Although the species distribution in the prevacation, postvacation, and control groups are comparable, the blood isolate group contains a much larger proportion of S. epidermidis.…”
Section: Discussionmentioning
confidence: 99%
“…Species identification has been done by ITS PCR, which has proven to be a reliable tool (8,16). Although the species distribution in the prevacation, postvacation, and control groups are comparable, the blood isolate group contains a much larger proportion of S. epidermidis.…”
Section: Discussionmentioning
confidence: 99%
“…A resistência dos ECN à vancomicina apesar de pouco freqüente, já é realidade no Brasil, conforme constatado em estudo 39 33 .…”
unclassified
“…It has been suggested that the mechanism of oxacillin resistance in S. saprophyticus may be other than the production of PBP2a. A study by Shittu et al (2006) in Ile-Ife, Nigeria also showed two S. saprophyticus isolated from the nose of medical personnel to exhibit resistance to oxacillin but lack mecA gene. In addition, whole genome sequence of S. saprophyticus has shown that its staphylococcus cassette chromosome (SCC) does not contain the mec antibiotic resistance determinant (Kuroda et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…The characterization of S. saprophyticus based on susceptibility to novobiocin 5µg used in this study is an important diagnostic tool in differentiating species of CoNS (Goldstein et al, 1983) and has been shown to have excellent correlation with molecular methods such as the 16S -23S rRNA intergenic spacer length polymorphism analysis by PCR (Shittu et al, 2006). The susceptibility of the S. saprophyticus isolates shows high resistance to commonly available antibiotics such as ampicillin, chloramphenicol, erythromycin and ceftriaxone, which are obtainable over-the-counter without medical prescription in Nigeria.…”
Section: Discussionmentioning
confidence: 99%